2002
DOI: 10.1074/jbc.m208494200
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone Stimulates Receptor Activator of NFκB Ligand and Inhibits Osteoprotegerin Expression via Protein Kinase A Activation of cAMP-response Element-binding Protein

Abstract: Parathyroid hormone (PTH) stimulates osteoclast formation by binding to its receptor on stromal/osteoblastic cells and stimulating the production of receptor activator of NFB ligand (RANKL) and inhibiting the expression of osteoprotegerin (OPG). However, the mechanisms through which PTH regulates these genes remain unknown. Here we report that PTH stimulated RANKL gene transcription and increased RANKL mRNA stability in murine stromal/osteoblastic cells stably expressing human PTH/PTH-related protein receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
191
1
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(210 citation statements)
references
References 56 publications
12
191
1
4
Order By: Relevance
“…The previous studies have shown that OPG production by osteoblasts is down-regulated by bone-resorbing factors such as 1,25(OH) 2 D 3 , PTH, and PGE 2 (38,(41)(42)(43)(44). Our results confirmed the previous finding that osteoclasts spontaneously form in the control cocultures containing OPG Ϫ/Ϫ osteoblasts.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The previous studies have shown that OPG production by osteoblasts is down-regulated by bone-resorbing factors such as 1,25(OH) 2 D 3 , PTH, and PGE 2 (38,(41)(42)(43)(44). Our results confirmed the previous finding that osteoclasts spontaneously form in the control cocultures containing OPG Ϫ/Ϫ osteoblasts.…”
Section: Discussionsupporting
confidence: 83%
“…6). Recently, Fu et al (38) reported that the activation of CREB by PTH is required for PTH-induced down-regulation of OPG expression. This suggests that the cAMP-PKA signals play a role in PGE 2 -induced suppression of OPG mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, hormones such as PTH [10] and glucocorticoids [11,12] have been reported to decrease OPG concentrations while anabolic agents such as estrogens, transforming growth factor β, related bone morphogenic factor and thrombopoietin [13][14][15][16] have been shown to enhance the OPG production in the osteoblastic and bone stromal cells. Recent studies [17][18][19] have described a bimodal pattern for the variation along the 24-h scale of circulating PTH, with a major peak during the night and a secondary peak in the late afternoon.…”
Section: Discussionmentioning
confidence: 99%
“…This pathway is known to induce TRANCE expression in osteoblasts following stimulation with PTH and PGE 2 [12][13][14]. Intracellular cAMP is generated by adenylate cyclase from adenosine triphosphate (ATP) as a substrate, whereas cAMP-specific phosphodiesterases (PDEs) degrade cAMP by hydrolysis [10,11].…”
Section: Introductionmentioning
confidence: 99%